Tourism and Sustainable Development - Gina Ionela Butnaru; Mirela Stefanica (CES Working Papers, 2014)
Tourism and sustainable development are the subject of many initiatives and public or private debates in Romania. The main problem to which these initiatives try to find an answer is mostly related to the income generation for the local communities by using rationally and efficiently the local potential, in agreement with the economic, social, natural, and cultural factors. Consequently, some measures should be taken, and the tourist sector as a whole needs all the methods of sustainable development: new technologies, change of social behaviour, change of environmental legislation, methods of environmental management, better planning and development of control procedures. In this article, we presented a model of tourism development which should be applied in all the regions of great tourist attraction, and we realised a synthesis of the socio-economic advantages of sustainable tourism.
Keywords: L83; Q01; 330; tourism; sustainable development; lasting development Romania